Polyunsaturated fatty acid deficiency affects sulfatides and other sulfated glycans in lysosomes through autophagy‐mediated degradation. Issue 7 (5th June 2020) - Wang, Yaping; Nakajima, Takero; Diao, Pan; Yamada, Yosuke; Nakamura, Kozo; Nakayama, Jun; Tanaka, Naoki; Aoyama, Toshifumi; Kamijo, Yuji
Abstract: Metabolic changes in sulfatides and other sulfated glycans have been related to various diseases, including Alzheimer's disease (AD). However, the importance of polyunsaturated fatty acids (PUFA) in sulfated lysosomal substrate metabolism and its related disorders is currently unknown. We investigated the effects of deficiency or supplementation of PUFA on the metabolism of sulfatides and sulfated glycosaminoglycans (sGAGs) in sulfatide‐rich organs (brain and kidney) of mice. A PUFA‐deficient diet for over 5 weeks significantly reduced the sulfatide expression by increasing the sulfatide degradative enzymes arylsulfatase A and galactosylceramidase in brain and kidney. This sulfatide degradation was clearly associated with the activation of autophagy and lysosomal hyperfunction, the former of which was induced by suppression of the Erk/mTOR pathway. A PUFA‐deficient diet also activated the degradation of sGAGs in the brain and kidney and that of amyloid precursor proteins in the brain, indicating an involvement in general lysosomal function and the early developmental process of AD. PUFA supplementation prevented all of the above abnormalities. Taken together, a PUFA deficiency might lead to sulfatide and sGAG degradation associated with autophagy activation and general lysosomal hyperfunction and play a role in many types of disease development, suggesting a possible benefit of prophylactic PUFA supplementation.